1986
DOI: 10.3758/bf03203005
|View full text |Cite
|
Sign up to set email alerts
|

Capture of stereopsis and apparent motion by illusory contours

Abstract: The removal of right-angle sectors from four circular black disks created the impression of a white "subjective" square with its four corners occluding the disks ("illusory contours"). The display in one eye was identical to that in the other except that for one eye a horizontal disparity was introduced between the edges of the cut sectors so that an illusory white square floated out in front of the paper. When a "template" ofthis stereogram was superimposed on a vertical squarewave grating (6 cycles/deg) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(31 citation statements)
references
References 32 publications
2
27
2
Order By: Relevance
“…Although results ostensibly similar to ours have been reported previously under dichoptic viewing conditions with a variety of stimulus patterns (e.g., Blomfield, 1973;Gregory & Harris, 1974;Harris & Gregory, 1973;Lawson, Cowan, Gibbs, & Whitmore, 1974;Ramachandran, 1986;Ramachandran & Cavanagh, 1985;Whitmore, Lawson, & Kozora, 1976), all of these studies used stimulus displays that contained monocular cues and a luminance mismatch or difference between the inducing elements and the illusory figure. In contrast, our results indicate that neither differences in luminance nor differences in temporal correlation (i.e., motion discontinuities) are necessary for the production of illusory contours.…”
supporting
confidence: 89%
“…Although results ostensibly similar to ours have been reported previously under dichoptic viewing conditions with a variety of stimulus patterns (e.g., Blomfield, 1973;Gregory & Harris, 1974;Harris & Gregory, 1973;Lawson, Cowan, Gibbs, & Whitmore, 1974;Ramachandran, 1986;Ramachandran & Cavanagh, 1985;Whitmore, Lawson, & Kozora, 1976), all of these studies used stimulus displays that contained monocular cues and a luminance mismatch or difference between the inducing elements and the illusory figure. In contrast, our results indicate that neither differences in luminance nor differences in temporal correlation (i.e., motion discontinuities) are necessary for the production of illusory contours.…”
supporting
confidence: 89%
“…Some preliminary observations suggested that illusory contours could be enhanced considerably by superimposing them on a checkerboard pattern ( Fig. 2) so that the edges of the pacmen are lined up with the edges of the checks (Ramachandran, 1986). We found that it was easier to make perceptual judgments on those "enhanced" illusory contours than on the more usual Kanizsa-type figures, i.e.…”
Section: Introductionmentioning
confidence: 57%
“…2). We found that this produced a striking enhancement of the illusory contours and a vivid impression of a square piece of checkerboard partially occluding four black disks in the background (Ramachandran, 1986(Ramachandran, , 1992. The enhancement is seen only when the edges of the checks are collinear with the edges of the "pacmen".…”
Section: : Contour Interactionsmentioning
confidence: 81%
See 1 more Smart Citation
“…Second, we assume that the images are taken under similar 108 The Problem of Achieving Full Correspondence illumination conditions. The first assumption enables us to apply the geometric results described in Part I, that is, recovering the epipolar geometry between the two views.…”
mentioning
confidence: 99%